Analisis Kebutuhan Modal Kerja pada Perusahaan Taufik Jaya Makmur di Samarinda - Rangga Tsabit Imam; Siti Masyithoh; Indra Suyoto Kurniawan (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
The purpose of this study was to determine the working capital available to meet working capital needs of the Company Taufik Jaya Makmur in Samarinda in 2016 to ensure the smooth operations of the company. This research method is quantitative descriptive. This study describes a list of production and operational costs of the Company Taufik Jaya Makmur.  Key informen in this study are employees of the Company Taufik Jaya Makmur. Analyzer used in this research is the calculation of the average value of each element of working capital, calculation of each element of working capital turnover, calculation of long rotation of each element of working capital, the calculation of the period of dependent working capital, the calculation of the speed of rotation of working capital and calculation working capital needs. Based on the research that has been done, it is known that in 2016 the working capital requirement increased to Rp 4.402.294.214 of  2015 is  Rp 1.921.636.363Keywords: Needs Working Capital, Method of Working Capital Turnover, Elements of Working Capital